2020
DOI: 10.24874/ti.861.03.20.06
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behaviour of Sansevieria and Carbon Fiber Reinforced Epoxy with Nanofillers: Taguchi Method

Abstract: Sliding wear behaviour of combined chemically modified Sansevieria and Carbon fiber reinforced epoxy (TSria/CF-E) and its multi-phase nanocomposite coupons has been carried out by Taguchi design of experiments. A Taguchi L16 orthogonal array and ANOVA were used to examine the consequence of tribo-system parameters on the tribological behaviour of hybrid TSria/CF-E composites filled with nano-CaCO3 and nano-SiC. The specific wear rate was calculated for each experiment for nano-CaCO3 and nano-SiC multi-phase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…These include jute-glass fiber-reinforced epoxy, 20 hemp–Kevlar–carbon fiber-reinforced epoxy, 21 and Sansevieria–carbon fiber-reinforced epoxy. 22 The results demonstrate that hybridization of synthetic fiber significantly improves the tribological behavior of NFPCs.…”
Section: Introductionmentioning
confidence: 83%
“…These include jute-glass fiber-reinforced epoxy, 20 hemp–Kevlar–carbon fiber-reinforced epoxy, 21 and Sansevieria–carbon fiber-reinforced epoxy. 22 The results demonstrate that hybridization of synthetic fiber significantly improves the tribological behavior of NFPCs.…”
Section: Introductionmentioning
confidence: 83%
“…42 Anjum et al observed that the normal load had the most impact on the specific wear rate of the modified sansevieria/carbon fiber reinforced epoxy filled with nano-CaCO 3 composite, whereas the filler loading had the most impact on the specific wear rate of the nano-SiC filled composites. 43 Manjunath and Rao reported that the coefficient of friction and wear rate of glass fiber-reinforced epoxy composites increased with increasing sliding speed and normal load, whereas the wear rate increased with increasing sliding distance. 44 For a range of filler contents (5–40 wt.%), Bhagyashekar and Rao found that the wear resistance and friction coefficient of epoxy composites increased with sliding distance and contact load.…”
Section: Introductionmentioning
confidence: 99%
“…Taguchi experimental design has been widely used to perform various kinds of tribological tests on metal, polymer and ceramic matrix composites [16][17]. Response surface method is also a powerful statistical and mathematical tool to predict the effect of wear test parameters on the specific wear rate [18][19].…”
Section: Introductionmentioning
confidence: 99%